2021
DOI: 10.2147/cmar.s308986
|View full text |Cite
|
Sign up to set email alerts
|

A miR-212-3p/SLC6A1 Regulatory Sub-Network for the Prognosis of Hepatocellular Carcinoma

Abstract: Introduction Hepatocellular carcinoma (HCC) is a liver cancer with a poor prognosis. Owing to the complexity and limited pathogenic mechanism research on HCC, the molecular targeted therapy has been hindered. Methods In this study, we categorized transcriptome data into low-Myc and high-Myc expression groups in 365 HCC samples, screened the differentially expressed RNAs, including 441 DE-lncRNAs, 99 DE-miRNAs and 612 DE-mRNAs, constructed a lncRNA-miRNA-mRNA regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…There is increasing evidence that abnormal DNA methylation plays an important role in the induction and development of CRC [ 40 , 41 ]. Although many studies have reported the dysregulation of SLC6A1 expression in many types of tumors, its potential mechanisms remained largely unclear [ 42 , 43 ]. In this study, a strong negative correlation between the SLC6A1 expression and SLC6A1 DNA methylation could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that abnormal DNA methylation plays an important role in the induction and development of CRC [ 40 , 41 ]. Although many studies have reported the dysregulation of SLC6A1 expression in many types of tumors, its potential mechanisms remained largely unclear [ 42 , 43 ]. In this study, a strong negative correlation between the SLC6A1 expression and SLC6A1 DNA methylation could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…32 These findings suggested that ZFPM2-AS1 and AC010280.2 might be potential therapeutic targets and prognostic biomarkers of HCC, and provided theoretical support for the prognostic prediction model constructed in this paper. At present, there are limited verifiable research results on the structure and function of the remaining lncRNA in the model and its role and mechanism in the occurrence and development of HCC, 33 and further exploration is needed. As an inflammation-related tumor, HCC has an immunosuppressive tumor TME, 34 which can promote immune tolerance through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…SLC6A1 is a gene for protein, a gamma-aminobutyric acid (GABA) transporter that localizes to the plasma membrane and is involved in synaptic signaling (Voisin et al, 2019). The SLC6A1 expression levels are correlated negatively with several significant immune cells (Zhang et al, 2021). ADCY encodes enzymes that catalyze cyclic AMP (cAMP) formation (Honoune & Defer, 2001).…”
Section: Discussionmentioning
confidence: 99%